Temporal-order judgement task suggests chronological action representations in motor experts and non-experts. Issue 11 (November 2020) - Harrison, Róisín Elaine; Giesel, Martin; Hesse, Constanze
Motor priming studies have suggested that human movements are mentally represented in the order in which they usually occur (i.e., chronologically). In this study, we investigated whether we could find evidence for these chronological representations using a paradigm which has frequently been employed to reveal biases in the perceived temporal order of events—the temporal-order judgement task. We used scrambled and unscrambled images of early and late movement phases from an everyday action sequence ("stepping") and an expert action sequence ("sprinting") to examine whether participants' mental representations of actions would bias their temporal-order judgements. In addition, we explored whether motor expertise mediated the size of temporal-order judgement biases by comparing the performances of sprinting experts with those of non-experts. For both action types, we found significant temporal-order judgement biases for all participants, indicating that there was a tendency to perceive images of human action sequences in their natural order, independent of motor expertise. Although there was no clear evidence that sprinting experts showed larger biases for sprinting action sequences than non-experts, considering sports expertise in a broader sense provided some tentative evidence for the idea that temporal-order judgement biases may be mediated by more general motor and/or perceptual familiarity with the running action rather than specific motor expertise.